Field emission measurement techniques for the optimisation of carbon nanotube cathodes. (15th November 2005) - Lysenkov, D.; Muller, G.
We have developed advanced measurement techniques for the investigation of the field emission (FE) properties of high-technology materials. Flat samples up to 30 mm in diameter can be optimised either for strong or weak electron emission, i.e., cold FE cathodes operating at field levels below 10 V/μm or high-voltage vacuum devices preventing FE up to 200 V/μm. The integral measurement system with luminescent screen (IMLS) provides a quick overview of the microscopic distribution and long- and short-term stability of the emission current, and facilitates a controlled conditioning of cold cathode samples at various pressures. The field emission scanning microscope (FESM) is incorporated within a UHV surface analysis system and enables high-resolution emitter distributions and local FE investigations down to the nanoscale. Exemplary results on carbon nanotube samples will be given to demonstrate that the combination of both instruments yields a very effective means for an improved understanding and tailoring of materials for cold cathode applications.